Determinants for ICT Adoption Among Small and Medium Enterprises in Pahang - R. Chandrashekar; Aziemahatul Hanim Ahmadon (Research in Management of Technology and Business, 2021)
In the new global economy, advent of the Information and Communication Technology (ICT) has revolutionized the way of doing commercial activities. It boosts firm’s reachability to information and access to experts, expansion of market and customer, increase exports, and improvement in managing organization. However, SMEs still lag in strategy development and implementation of ICT adoption in their business. Therefore, the purpose of this study to investigate the determinant and strategy of ICT adoption among SMEs. The study was focusing on the small and medium enterprise in Pahang. The study employed quantitative method and data will be collected by distributing questionnaires to respondents. The data will be analyzed by using Statistical Package for Social Science (SPSS). Most of the respondents agree with the internal factor is management support and commitment while external factor is competitiveness of environment (need to stay competitive). The strategies are increasing the public spending on technology projects for government, lending programs for SMEs for non-governmental organizations and SME should attending in computerization projects meetings frequently. Based on the result and finding, the two research objectives in this research have successfully achieved. SME Malaysia need to consider the internal factor and external factor in ICT adoption and the strategies from the government, NGO and SME to ensure that they can implement the technology and ICT in their business.